The Follicular Benignancy- Desmoplastic Trichoepithelioma - Bajaj Anubha (Journal of Clinical and Diagnostic Pathology, 2020)
Trichoepithelioma is a benign, cutaneous neoplasm originating from the hair follicle and is categorized into singular trichoepithelioma, multiple trichoepithelioma and desmoplastic trichoepithelioma wherein desmoplastic trichoepithelioma is cogitated as an exceptional, cutaneous adnexal tumour. Desmoplastic trichoepithelioma was initially scripted by Hartzell in 1904 wherein the lesion was described as a benign, cystic epithelioma. Desmoplastic trichoepithelioma can be additionally nomenclated as epithelioma adenoides cysticum, morphea - like epithelioma or sclerosing epithelial hamartoma 1. Familial instances of desmoplastic trichoepithelioma are infrequent and can be misdiagnosed on account of adjunctive benign, cutaneous, adnexal neoplasms depicting subtle clinical features, excepting a nodular basal cell carcinoma. Cogent clinical and histological features can assist the diagnosis of desmoplastic trichoepithelioma 12.
Keywords: CYLD genomic mutation